TINGKAT KOMPETENSI INDIVIDU DALAM BERMEDIA TELEVISI PADA ORGANISASI KARANG TARUNA KABUPATEN SIAK - Satryo, Windra Alfathan; Yesicha, Chelsy (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
At present there are many television shows that are less educational and unbalanced information for the audience. This of course makes the audience who watch television become affected. Even the programs presented sometimes contain elements of violation of broadcasting behavior guidelines and broadcast program standards (PPP-SPS). Based on the problems caused by the impact of television media, the need for education is related to understanding television mass media for the community by providing an understanding of television media literacy. The Riau Regional Indonesian Broadcasting Commission implemented a television media literacy socialization program. The socialization activity aims to understand the right media, respond to the media correctly and take sides with the right media content. The purpose of this study was to find out the effects generated from media literacy dissemination activities by looking at the extent to which individual competency levels in television media were members of the Tarak Karang Siak Regency.This study uses quantitative research methods. The sample in this study amounted to 70 respondents who participated in television media literacy socialization activities. Data collection techniques carried out were spread questionnaires and documentation. Data analysis techniques use the percentage statistical formula.The results showed that the level of individual competence in television media at the Tarak Regency organization in Siak Regency was in the advanced level category with a score of 51.4%. This shows that the level of individual competency in television media for members of the Tarak Karang Siak Regency has been very good.Keywords: Television, Media Literacy, Media Literacy Socialization, Individual Competency Level